Teaching Persian to Non-Iranian Language Learners: Teachers' attitude towards the use of literary texts - Amirreza Vakilifard; Mohammad Taghi Rad (مطالعات زبانی و بلاغی)
Just as our inner attitudes influence our behavior, our educational attitudes affect our classroom behaviors, including the choice of curriculum content. One of the issues in the Persian language didactic is the use of literary texts in Persian language classes for non-Iranian learners. This study examines teachers' attitudes toward the use of literary texts in teaching Persian to speakers of other languages. A 45-item questionnaire was used for this purpose. The participants in the survey were 26 teachers of the Persian language. The results indicate that the use of literary texts has a positive and significant role in the teaching of the Persian language to speakers of other languages. Findings show that words and symbols used in literary texts are difficult for Persian language learners. Literary texts are dysfunctional to develop language skills such as speaking, writing, and listening. But it improves reading skills and vocabulary. From the teachers' perspective, cultural and social environments in literary texts are unfamiliar to Persian language learners, and it is difficult to identify the cultural references and symbols used in Persian literary texts, but they can lead to the understanding of Persian's cultural norms and customs. The teachers prioritize storytelling for classroom use. Likewise, the findings suggest that gender, age, educational background, and teaching history do not influence the teachers' attitudes about the role of literary texts in teaching the Persian language to speakers of other languages.